2001
DOI: 10.1111/j.1349-7006.2001.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Muscle Cells Causes Weight Loss Prior to Impairment of DNA Synthesis in Tumor‐bearing Rabbits

Abstract: The mechanism of weight loss induced by the growth of malignant tumors is still unknown. We investigated it by focusing on apoptosis of skeletal muscle. VX2-tumor was implanted into rabbits and the apoptotic index (AI) of skeletal muscle was measured by in situ end-labeling assay. Plasma of the tumor-bearing rabbits was perfused repeatedly through non-coated charcoal resin. The AI reached 54.6% early after tumor implantation, when weight loss amounted to an 18% decrease in lean body mass (LBM) without change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…A decrease in the apoptotic index has also been reported in the late stages of cancer cachexia. In rabbits with cancer cachexia, there is an increase in the apoptotic index in the early stages of cachexia but a decrease at higher losses [63]. The expression of Bax, which promotes apoptosis, is also increased in the early stage of weight loss, but thereafter declines.…”
Section: Muscle Cell Death In Cardiac Cachexiamentioning
confidence: 98%
“…A decrease in the apoptotic index has also been reported in the late stages of cancer cachexia. In rabbits with cancer cachexia, there is an increase in the apoptotic index in the early stages of cachexia but a decrease at higher losses [63]. The expression of Bax, which promotes apoptosis, is also increased in the early stage of weight loss, but thereafter declines.…”
Section: Muscle Cell Death In Cardiac Cachexiamentioning
confidence: 98%
“…Fragmentation of poly(ADP-ribose) polymerase (PARP) was also observed, which is cleaved during apoptosis by caspases -3 and -7, although there was no evidence for DNA fragmentation into a nucleosomal ladder typical of apoptosis. However, enhanced laddering of DNA was observed in the skeletal muscle of rats bearing the Yoshida AH-130 ascites hepatoma, mice bearing the Lewis lung carcinoma (266), and rabbits bearing the UX2 tumor (113), indicative of apoptosis. The expression of Bax, which promotes apoptosis, was also increased in the early stages of weight loss.…”
Section: Apoptosis In Skeletal Musclementioning
confidence: 99%
“…Ishiko et al (113) proposed two mechanisms for muscle depletion during tumor growth: apoptosis in the early stages and metabolic abnormalities in the late stage. An increased activity of caspases-1, -3, -6, -8, and -9 was observed in gastrocnemius muscle of mice bearing the cachexia-inducing MAC16 tumor (17).…”
Section: Apoptosis In Skeletal Musclementioning
confidence: 99%
“…The results showed that LBM and body fat began to decrease in the early stage after implantation, when the pathological manifestations of cachexia were still not marked. We have also reported the occurrence of apoptosis of normal skeletal muscle in the early stage of tumor bearing, 8) and in the present study we investigated its pathogenetic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported observing that apoptosis occurs in normal skeletal muscle cell of VX2-bearing rabbits in the early stage after tumor implantation. 8) Apoptosis plays a key role in various biological processes and functions and is observed in many different tumor and normal tissues. Various genes related to apoptosis have already been identified, and one of them, bcl-2, is known to be a suppressor of apoptosis.…”
mentioning
confidence: 99%